Clinical and angiographic profile in patients of western Rajasthan undergoing percutaneous coronary interventions: a single centre experience - Sanghvi, Sanjeev; Kumar, Aditya; Mathur, Rohit; Baroopal, Anil (International Journal of Research in Medical Sciences, 2018)
Background: This study was aimed to evaluate clinical and angiographic profile of patients undergoing percutaneous coronary intervention at the Department of Cardiology, Mathura Das Mathur (MDM) Hospital attached to Dr. Sampurnanand Medical College, Jodhpur. Methods: This study was hospital based prospective observational study conducted in the department of cardiology at MDM hospital. This study included 1166 patients who underwent percutaneous coronary intervention at cardiac cathlab of MDM hospital from January 2016 to April 2017. Procedural details noted included vascular access route, lesion characteristics, number of lesions intervened, stents used and periprocedural pharmacotherapy administered. Results: A total of 1166 patients (mean age- 56.3±10.4 years) with 76.5% male and 23.5% female were included in the study. Smoking and hypertension were the most common risk factors, present in 64% and 56% patients respectively. Diabetes mellitus and obesity were observed in 24.5% , 18.0% patients respectively. Anterior wall MI was the most common mode of presentation (36.2%). Single Vessel Disease (SVD) was the most common angiographic pattern observed in 62% patients; left anterior descending artery (LAD) was the most frequently involved vessel (65.9%); and type B lesions were most prevalent (48%). Most of the procedures were elective (61.4%) and femoral route was used in the majority (76%). Radial access was obtained in 24% of patients. Primary PCI was done in 6% of cases while pharmaco-invasive approach was adopted in 32.6% of patients. Drug eluting stents were deployed in 100% of the cases. The overall procedural success rate was 95.4%. Procedural mortality was nil and periprocedural complications occurred in 16.0% patients. Conclusions: This first PCI study from western Rajasthan provides an overview into the salient features of CAD among regional population and focus on the characteristics of PCIs performed with their outcomes.